Sound-absorbing cotton for automobile interior and preparation process thereof

By adding nanoporous particles and other components to the sound-absorbing cotton for car interiors and using twin-screw extrusion and needle-punching technology, the shortcomings of the existing sound-absorbing cotton in noise control are solved, achieving more efficient sound absorption effect and thermal insulation performance, and improving the comfort and tranquility of the car interiors.

CN119264628BActive Publication Date: 2025-04-29YONGFANGYE FIBER PROD (CHANGSHU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411822729.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing sound-absorbing cotton for automotive interiors has shortcomings in reducing noise levels and cannot fully meet consumers' needs for improving car interior comfort and noise control.

Method used

A sound-absorbing cotton for automotive interiors is adopted, and its composition includes polylactic acid, surfactant, heat stabilizer, nanoporous particles, active calcium silicate, silicone oil and tributyl citrate. Through specific preparation processes such as twin-screw extrusion and needle puncture technology, an efficient sound-absorbing material is formed.

Benefits of technology

It significantly improves the sound absorption effect and thermal insulation performance of sound-absorbing cotton, can effectively absorb and reduce the propagation and reflection of sound waves, and improves the tranquility and comfort of the interior environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264628B_ABST
    Figure CN119264628B_ABST
Patent Text Reader

Abstract

The present invention discloses a sound-absorbing cotton for automobile interior and a preparation process thereof, which relates to the technical field of automobile interior, and is made of the following components: polylactic acid, surfactant, heat stabilizer, nanoporous particles, active calcium silicate, silicone oil, and acetyl tributyl citrate; the sound-absorbing cotton prepared by the present invention is a highly efficient sound-absorbing material, which can be well applied to automobile interior to improve the noise reduction effect. Through its unique organizational structure, it can effectively absorb and reduce the propagation and reflection of sound, and improve the noise reduction effect. When sound waves enter the sound-absorbing cotton prepared by the present invention, the fiber structure inside it will generate friction and vibration with the air, and then convert the sound energy into heat energy for consumption. Through continuous consumption, excellent sound absorption and noise reduction effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of automobile interior decoration, in particular to a sound-absorbing cotton for automobile interior decoration and a preparation process thereof. Background Art

[0002] With the rapid development of modern society, people's demand for travel is becoming more and more frequent. Therefore, the demand for cars is constantly increasing, prompting the automobile industry to become one of the important pillars of the national economy. While people are pursuing driving experience and riding comfort, their requirements for noise control in the interior environment of the car are also increasing. In this context, sound-absorbing cotton for automotive interiors came into being and became one of the key materials for improving the quality of the interior environment of the car.

[0003] As the urbanization process continues to accelerate and road traffic becomes increasingly busy, noise pollution problems such as engine noise, tire rolling noise and wind noise generated during vehicle driving are becoming more and more serious. These noises not only affect the driver's mood and concentration, but also may pose a potential threat to the physical and mental health of passengers.

[0004] Therefore, how to effectively reduce the noise level inside the car and create a quiet and comfortable driving space has become one of the current requirements for improving automobile quality.

[0005] Sound-absorbing cotton is a product that is currently widely used. It can reduce noise to a certain extent. At the same time, the domestic automobile market is in a period of rapid growth, and consumers' requirements for automobile quality and comfort are constantly increasing, which provides a broad market space for the development of sound-absorbing cotton for automobile interiors.

[0006] In order to further improve the sound absorption performance of sound-absorbing cotton, based on this, a sound-absorbing cotton for automobile interior and a preparation process thereof are provided to solve the existing technical problems. Summary of the invention

[0007] The purpose of the present invention is to provide a sound-absorbing cotton for automobile interior decoration and a preparation process thereof, so as to solve the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A sound-absorbing cotton for automobile interior decoration comprises the following components by weight: 70-85 parts of polylactic acid, 1-2 parts of surfactant, 2-3 parts of heat stabilizer, 15-18 parts of nanoporous particles, 6-8 parts of active calcium silicate, 2-4 parts of silicone oil and 5-6 parts of acetyl tributyl citrate.

[0010] As a further technical solution: the surfactant is fatty acid methyl ester polyoxyethylene ether.

[0011] As a further technical solution: the method for preparing nanoporous particles comprises the following steps:

[0012] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0013] Among them, SiO 2 The mass ratio of the nanoparticles to cyanamide is 1:2-2.5;

[0014] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10-15 minutes, then the temperature is further raised to 240°C, and the temperature is kept at this temperature for 10-15 minutes. Then the temperature is further raised to 390°C, and the temperature is kept at this temperature for 15-20 minutes. Finally, the temperature is raised to 520°C, and the temperature is kept at this temperature for 30-40 minutes. The mixed material is naturally cooled to room temperature to obtain a calcined material.

[0015] (3) etching the calcined material to obtain a nano-etched material;

[0016] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0017] Wherein, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15-20g:150mL;

[0018] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0019] As a further technical solution: in step (2), the inert gas is nitrogen;

[0020] The heating rate is 10°C / min.

[0021] As a further technical solution: the etching process is:

[0022] First, prepare the etching solution:

[0023] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0024] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3-4 hours, and then the material is discharged, washed with water until neutral, and dried to obtain the product.

[0025] As a further technical solution: the concentration of the ammonium bifluoride solution is 3.5 mol / L;

[0026] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20-24 g: 100 mL;

[0027] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0028] The drying temperature was 50°C and the drying time was 2 hours.

[0029] As a further technical solution: the mass fraction of the organic silane coupling agent solution is 10%;

[0030] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0031] As a further technical solution: in step (5), the high-speed centrifugal speed is 9000 r / min;

[0032] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0033] As a further technical solution: the heat stabilizer is calcium stearate.

[0034] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0035] (1) Weigh each component raw material according to its weight;

[0036] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0037] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0038] The melt temperature in the twin-screw extruder is 235°C;

[0039] The diameter of the sound-absorbing cotton is 4μm.

[0040] Beneficial effects:

[0041] The sound-absorbing cotton prepared by the invention is a highly efficient sound-absorbing material and can be well applied to automobile interior decoration to improve the noise reduction effect.

[0042] Through its unique organizational structure, it can effectively absorb and reduce the propagation and reflection of sound, and improve the noise reduction effect. When the sound wave enters the sound-absorbing cotton prepared by the present invention, the fiber structure inside it will produce friction and vibration with the air, and then convert the sound energy into heat energy for consumption. Through continuous consumption, excellent sound absorption and noise reduction effect is achieved.

[0043] At the same time, the sound-absorbing cotton prepared by the present invention is applied to automobile interior decoration and also has excellent thermal insulation performance, can effectively isolate external heat and keep the temperature inside the car stable.

[0044] Sound-absorbing cotton is a kind of man-made fiber. A large number of fibers are entangled with each other to form a multi-layer structure with a large number of small gaps. This structure enables sound waves to be effectively scattered and absorbed when passing through the sound-absorbing cotton, thereby reducing the reflection and propagation of sound.

[0045] The fiber structure of the sound-absorbing cotton constitutes a large number of tiny pores inside it. When sound waves are incident on the sound-absorbing cotton, these pores will scatter the sound waves, causing the sound waves to be reflected and refracted multiple times inside the material, thereby increasing the contact area between the sound waves and the material. At the same time, the presence of pores also allows the energy of the sound waves to be effectively absorbed and converted inside the material, further reducing the reflection and propagation of the sound waves. In order to further enhance the sound absorption effect of the sound-absorbing cotton prepared by the present invention, the present invention introduces nanoporous particles into its raw materials. The nanoporous structure is evenly distributed in the sound-absorbing cotton tissue structure, which can increase the contact points inside the material and form a large number of closed cavities. After the sound waves enter a large number of cavities, they will be continuously reflected in the cavities, consuming sound energy, making the sound waves more easily absorbed and converted during the propagation process, thereby greatly improving the sound absorption effect of the sound-absorbing cotton on the sound waves and improving the sound absorption and noise reduction function of the sound-absorbing cotton.

[0046] The sound-absorbing effect of sound-absorbing cotton is also related to its thickness. Generally speaking, a larger thickness can increase the propagation distance of sound waves inside the material, giving sound waves more opportunities to interact with the material, thereby improving the sound-absorbing effect. Therefore, the thickness of the sound-absorbing cotton can be appropriately increased according to the specific conditions of the car interior to further improve the sound-absorbing effect of the sound-absorbing cotton. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is the sample diagram of Example 1. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] A sound-absorbing cotton for automobile interior decoration comprises the following components by weight: 70-85 parts of polylactic acid, 1-2 parts of surfactant, 2-3 parts of heat stabilizer, 15-18 parts of nanoporous particles, 6-8 parts of active calcium silicate, 2-4 parts of silicone oil and 5-6 parts of acetyl tributyl citrate.

[0050] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0051] The method for preparing nanoporous particles comprises the following steps:

[0052] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0053] Among them, SiO 2 The mass ratio of the nanoparticles to cyanamide is 1:2-2.5;

[0054] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10-15 minutes, then the temperature is further raised to 240°C, and the temperature is kept at this temperature for 10-15 minutes. Then the temperature is further raised to 390°C, and the temperature is kept at this temperature for 15-20 minutes. Finally, the temperature is raised to 520°C, and the temperature is kept at this temperature for 30-40 minutes. The mixed material is naturally cooled to room temperature to obtain a calcined material.

[0055] (3) etching the calcined material to obtain a nano-etched material;

[0056] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0057] Wherein, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15-20g:150mL;

[0058] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0059] In step (2), the inert gas is nitrogen;

[0060] The heating rate is 10°C / min.

[0061] The etching process is:

[0062] First, prepare the etching solution:

[0063] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0064] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3-4 hours, and then the material is discharged, washed with water until neutral, and dried to obtain the product.

[0065] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0066] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20-24 g: 100 mL;

[0067] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0068] The drying temperature was 50°C and the drying time was 2 hours.

[0069] The mass fraction of the organic silane coupling agent solution is 10%;

[0070] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0071] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0072] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0073] The heat stabilizer is calcium stearate.

[0074] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0075] (1) Weigh each component raw material according to its weight;

[0076] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0077] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0078] The melt temperature in the twin-screw extruder is 235°C;

[0079] The diameter of the sound-absorbing cotton is 4μm.

[0080] The active calcium silicate parameters used are:

[0081]

[0082] The following are specific embodiments: Example 1

[0083] A preparation process of sound-absorbing cotton for automobile interior decoration, calculated by weight:

[0084]

[0085] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0086] The method for preparing nanoporous particles comprises the following steps:

[0087] (1) First, SiO 2The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0088] Among them, SiO 2 The mass ratio of nanoparticles to cyanamide was 1:2;

[0089] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10 minutes, then the temperature is further raised to 240°C and kept at this temperature for 10 minutes, then the temperature is further raised to 390°C and kept at this temperature for 15 minutes, and finally the temperature is raised to 520°C and kept at this temperature for 30 minutes, and then naturally cooled to room temperature to obtain a calcined material;

[0090] (3) etching the calcined material to obtain a nano-etched material;

[0091] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0092] Among them, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15g:150mL;

[0093] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0094] In step (2), the inert gas is nitrogen;

[0095] The heating rate is 10°C / min.

[0096] The etching process is:

[0097] First, prepare the etching solution:

[0098] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0099] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3 hours, and then the material is discharged, washed with water until neutral, and dried to obtain.

[0100] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0101] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20 g: 100 mL;

[0102] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0103] The drying temperature was 50°C and the drying time was 2 hours.

[0104] The mass fraction of the organic silane coupling agent solution is 10%;

[0105] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0106] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0107] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0108] The heat stabilizer is calcium stearate.

[0109] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0110] (1) Weigh each component raw material according to its weight;

[0111] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0112] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0113] The melt temperature in the twin-screw extruder is 235°C;

[0114] The diameter of the sound-absorbing cotton is 4μm. Example 2

[0115] A preparation process of sound-absorbing cotton for automobile interior decoration, calculated by weight:

[0116]

[0117] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0118] The method for preparing nanoporous particles comprises the following steps:

[0119] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0120] Among them, SiO 2 The mass ratio of nanoparticles to cyanamide was 1:2;

[0121] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10 minutes, then the temperature is further raised to 240°C and kept at this temperature for 10 minutes, then the temperature is further raised to 390°C and kept at this temperature for 15 minutes, and finally the temperature is raised to 520°C and kept at this temperature for 30 minutes, and then naturally cooled to room temperature to obtain a calcined material;

[0122] (3) etching the calcined material to obtain a nano-etched material;

[0123] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0124] Among them, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15g:150mL;

[0125] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0126] In step (2), the inert gas is nitrogen;

[0127] The heating rate is 10°C / min.

[0128] The etching process is:

[0129] First, prepare the etching solution:

[0130] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0131] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3 hours, and then the material is discharged, washed with water until neutral, and dried to obtain.

[0132] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0133] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20 g: 100 mL;

[0134] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0135] The drying temperature was 50°C and the drying time was 2 hours.

[0136] The mass fraction of the organic silane coupling agent solution is 10%;

[0137] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0138] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0139] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0140] The heat stabilizer is calcium stearate.

[0141] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0142] (1) Weigh each component raw material according to its weight;

[0143] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0144] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0145] The melt temperature in the twin-screw extruder is 235°C;

[0146] The diameter of the sound-absorbing cotton is 4μm. Example 3

[0147] A preparation process of sound-absorbing cotton for automobile interior decoration, calculated by weight:

[0148]

[0149] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0150] The method for preparing nanoporous particles comprises the following steps:

[0151] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0152] Among them, SiO 2 The mass ratio of nanoparticles to cyanamide was 1:2;

[0153] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10 minutes, then the temperature is further raised to 240°C and kept at this temperature for 10 minutes, then the temperature is further raised to 390°C and kept at this temperature for 15 minutes, and finally the temperature is raised to 520°C and kept at this temperature for 30 minutes, and then naturally cooled to room temperature to obtain a calcined material;

[0154] (3) etching the calcined material to obtain a nano-etched material;

[0155] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0156] Among them, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15g:150mL;

[0157] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0158] In step (2), the inert gas is nitrogen;

[0159] The heating rate is 10°C / min.

[0160] The etching process is:

[0161] First, prepare the etching solution:

[0162] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0163] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3 hours, and then the material is discharged, washed with water until neutral, and dried to obtain.

[0164] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0165] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20 g: 100 mL;

[0166] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0167] The drying temperature was 50°C and the drying time was 2 hours.

[0168] The mass fraction of the organic silane coupling agent solution is 10%;

[0169] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0170] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0171] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0172] The heat stabilizer is calcium stearate.

[0173] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0174] (1) Weigh each component raw material according to its weight;

[0175] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0176] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0177] The melt temperature in the twin-screw extruder is 235°C;

[0178] The diameter of the sound-absorbing cotton is 4μm. Example 4

[0179] A preparation process of sound-absorbing cotton for automobile interior decoration, calculated by weight:

[0180]

[0181] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0182] The method for preparing nanoporous particles comprises the following steps:

[0183] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0184] Among them, SiO 2 The mass ratio of nanoparticles to cyanamide was 1:2;

[0185] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10 minutes, then the temperature is further raised to 240°C and kept at this temperature for 10 minutes, then the temperature is further raised to 390°C and kept at this temperature for 15 minutes, and finally the temperature is raised to 520°C and kept at this temperature for 30 minutes, and then naturally cooled to room temperature to obtain a calcined material;

[0186] (3) etching the calcined material to obtain a nano-etched material;

[0187] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0188] Among them, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15g:150mL;

[0189] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0190] In step (2), the inert gas is nitrogen;

[0191] The heating rate is 10°C / min.

[0192] The etching process is:

[0193] First, prepare the etching solution:

[0194] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0195] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3 hours, and then the material is discharged, washed with water until neutral, and dried to obtain.

[0196] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0197] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20 g: 100 mL;

[0198] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0199] The drying temperature was 50°C and the drying time was 2 hours.

[0200] The mass fraction of the organic silane coupling agent solution is 10%;

[0201] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0202] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0203] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0204] The heat stabilizer is calcium stearate.

[0205] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0206] (1) Weigh each component raw material according to its weight;

[0207] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0208] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0209] The melt temperature in the twin-screw extruder is 235°C;

[0210] The diameter of the sound-absorbing cotton is 4μm. Example 5

[0211] A preparation process of sound-absorbing cotton for automobile interior decoration, calculated by weight:

[0212]

[0213] The surfactant is fatty acid methyl ester polyoxyethylene ether.

[0214] The method for preparing nanoporous particles comprises the following steps:

[0215] (1) First, SiO 2 The nanoparticles and cyanamide are uniformly mixed to obtain a mixture;

[0216] Among them, SiO 2 The mass ratio of nanoparticles to cyanamide was 1:2;

[0217] (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10 minutes, then the temperature is further raised to 240°C and kept at this temperature for 10 minutes, then the temperature is further raised to 390°C and kept at this temperature for 15 minutes, and finally the temperature is raised to 520°C and kept at this temperature for 30 minutes, and then naturally cooled to room temperature to obtain a calcined material;

[0218] (3) etching the calcined material to obtain a nano-etched material;

[0219] (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion;

[0220] Among them, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15g:150mL;

[0221] (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

[0222] In step (2), the inert gas is nitrogen;

[0223] The heating rate is 10°C / min.

[0224] The etching process is:

[0225] First, prepare the etching solution:

[0226] Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution;

[0227] The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3 hours, and then the material is discharged, washed with water until neutral, and dried to obtain.

[0228] The concentration of ammonium bifluoride solution is 3.5 mol / L;

[0229] The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20 g: 100 mL;

[0230] The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C;

[0231] The drying temperature was 50°C and the drying time was 2 hours.

[0232] The mass fraction of the organic silane coupling agent solution is 10%;

[0233] Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

[0234] In step (5), the high-speed centrifugal speed is 9000 r / min;

[0235] Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

[0236] The heat stabilizer is calcium stearate.

[0237] A preparation process of sound-absorbing cotton for automobile interior decoration, comprising the following steps:

[0238] (1) Weigh each component raw material according to its weight;

[0239] (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture;

[0240] (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²;

[0241] The melt temperature in the twin-screw extruder is 235°C;

[0242] The diameter of the sound-absorbing cotton is 4μm.

[0243] Comparative Example 1:

[0244] The difference from Example 1 is that no nanoporous particles are added, and the rest of the technical solutions remain unchanged.

[0245] Comparative Example 2

[0246] The difference from Example 1 is that the etching process is not performed during the preparation of the nanoporous particles, and the rest of the technical solutions remain unchanged.

[0247] test:

[0248] The sound absorption coefficient of the sound absorbing material was tested using the standing wave tube method, and the test was performed in accordance with GB / T 18696.2-2002, and the sound absorption coefficients of the embodiment and the comparative example samples with the same area and thickness of 5 mm at 1000 Hz were compared;

[0249] Table 1

[0250]

[0251] It can be seen from Table 1 that the sound-absorbing cotton prepared by the present invention has a higher sound absorption coefficient.

[0252] Taking Example 1 as the basic sample, the sound absorption coefficients in different frequency ranges are compared:

[0253] Table 2

[0254]

[0255] It can be seen from Table 2 that with the increase of frequency, the sound absorption coefficient of the sound-absorbing cotton of the present invention continues to increase.

[0256] By conducting a sound insulation test on the samples of the embodiment and the comparative example with equal areas, the samples are used to block the generating room and the testing room, the decibel of the sound is detected in the generating room, and T1 is recorded, and the decibel of the sound is tested in the testing room, and T2 is recorded. The sound insulation is T1-T2:

[0257] Table 3

[0258]

[0259] It can be seen from Table 3 that the sound-absorbing cotton prepared by the present invention has excellent sound insulation effect.

[0260] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A sound-absorbing cotton for automobile interior, characterized in that: The following components are included by weight: 70-85 parts of polylactic acid, 1-2 parts of surfactant, 2-3 parts of heat stabilizer, 15-18 parts of nanoporous particles, 6-8 parts of active calcium silicate, 2-4 parts of silicone oil, and 5-6 parts of acetyl tributyl citrate; The method for preparing nanoporous particles comprises the following steps: (1) First, SiO2 nanoparticles and cyanamide are uniformly mixed to obtain a mixture; The mass ratio of SiO2 nanoparticles to cyanamide is 1:2-2.5; (2) Under the protection of an inert atmosphere, the mixed material is heated. When the temperature rises to 150°C, it is kept at this temperature for 10-15 minutes, then the temperature is further raised to 240°C, and the temperature is kept at this temperature for 10-15 minutes. Then the temperature is further raised to 390°C, and the temperature is kept at this temperature for 15-20 minutes. Finally, the temperature is raised to 520°C, and the temperature is kept at this temperature for 30-40 minutes. The mixed material is naturally cooled to room temperature to obtain a calcined material. (3) etching the calcined material to obtain a nano-etched material; (4) dispersing the nano-etching material in the organic silane coupling agent solution and continuously stirring for 72 hours to obtain a dispersion; Wherein, the mixing ratio of nano-etching material and organic silane coupling agent solution is 15-20g:150mL; (5) Using a centrifuge to perform high-speed centrifugation for 20 minutes, followed by filtration, washing, and then freeze-drying to remove residual water to obtain nanoporous particles.

2. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: The surfactant is fatty acid methyl ester polyoxyethylene ether.

3. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: In step (2), the inert gas is nitrogen; The heating rate is 10°C / min.

4. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: The etching process is as follows: First, prepare the etching solution: Adding ammonium bifluoride to deionized water, stirring and mixing to obtain an ammonium bifluoride solution; The nano-etching material and the ammonium bifluoride solution are sequentially added into a vacuum impregnation reactor, and then stirred for reaction for 3-4 hours, and then the material is discharged, washed with water until neutral, and dried to obtain the product.

5. The sound-absorbing cotton for automobile interior decoration according to claim 4, characterized in that: The concentration of the ammonium bifluoride solution is 3.5 mol / L; The mixing ratio of the nano-etching material and the ammonium bifluoride solution is 20-24 g: 100 mL; The vacuum degree in the vacuum impregnation reactor is 0.2 Pa and the temperature is 80°C; The drying temperature was 50°C and the drying time was 2 hours.

6. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: The mass fraction of the organic silane coupling agent solution is 10%; Wherein, the organic silane coupling agent is vinyl tri(β-methoxyethoxy) silane.

7. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: In step (5), the high-speed centrifugal speed is 9000 r / min; Freeze drying was performed by prefreezing at -80°C for 0.5 h and then vacuum pumping for 4 h.

8. The sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: The heat stabilizer is calcium stearate.

9. The preparation process of the sound-absorbing cotton for automobile interior decoration according to claim 1, characterized in that: The following steps are involved: (1) Weigh each component raw material according to its weight; (2) Add each component to a mixer and mix them evenly to obtain a uniform mixture; (3) Add the uniform mixture into a twin-screw extruder for melt extrusion, and then spin through a nozzle to obtain fibers, and then needle punch to obtain a sound-absorbing cotton cloth with a surface density of 520 g / ㎡ and a needle punching density of 268 needles / cm²; The melt temperature in the twin-screw extruder is 235°C; The diameter of the sound-absorbing cotton is 4μm.

Citation Information

Patent Citations

  • Ordered hierarchical porous graphite-phase carbon nitride photocatalytic material preparation method

    CN109126852A

  • Noise-reducing sound-absorbing cotton and preparation method thereof

    CN116653384A